2014
DOI: 10.1186/1480-9222-16-11
|View full text |Cite|
|
Sign up to set email alerts
|

The functional role of long non-coding RNAs and epigenetics

Abstract: Long non-coding RNAs (lncRNAs) are non-protein coding transcripts longer than 200 nucleotides. The post-transcriptional regulation is influenced by these lncRNAs by interfering with the microRNA pathways, involving in diverse cellular processes. The regulation of gene expression by lncRNAs at the epigenetic level, transcriptional and post-transcriptional level have been well known and widely studied. Recent recognition that lncRNAs make effects in many biological and pathological processes such as stem cell pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
202
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(215 citation statements)
references
References 192 publications
(202 reference statements)
0
202
0
5
Order By: Relevance
“…Moreover, functional analyses have revealed that lncRNAs play essential roles in a range of developmental processes , SuNing Huang 1 , Gang Chen 2 * and diseases, including tumorigenesis and metastasis (Gupta et al, 2010;Cao, 2014;Liu et al, 2014). Aberrantly expressed lncRNAs are a hallmark of carcinomas, suggesting their potential application as predictive and prognostic biomarkers (Li et al, 2014;Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, functional analyses have revealed that lncRNAs play essential roles in a range of developmental processes , SuNing Huang 1 , Gang Chen 2 * and diseases, including tumorigenesis and metastasis (Gupta et al, 2010;Cao, 2014;Liu et al, 2014). Aberrantly expressed lncRNAs are a hallmark of carcinomas, suggesting their potential application as predictive and prognostic biomarkers (Li et al, 2014;Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Należy podkreślić ich znaczenie w modyfikacji chromatyny, transkrypcji, procesach potranskrypcyjnych oraz rozwoju nowotworów. Prowadzone badania dostarczają informacji odnośnie do możliwości wykorzystania ncRNA w terapii, jako potencjalnych biomarkerów w diagnostyce chorób o podłożu nowotworowym [35,36,37].…”
Section: Niekodujące Cząsteczki Rnaunclassified
“…HOTAIR (HOX antisense intergenic RNA) w raku piersi, wątroby, trzustki, PCGEM1 (Prostate Specific Gene 1), DD3 (Differential Display Code 3), PCNCR1 (Prostate Cancer Non-Coding RNA 1) w raku prostaty [35,37]. Fenotypowo-specyficzna ekspresja lncRNA oraz ich stopień zaangażowania w proces nowotworzenia sprawiają, że czą-steczki te są idealnymi kandydatami na biomarkery w diagnostyce i terapii nowotworów.…”
Section: Długie Niekodujące Cząsteczki Rnaunclassified
See 1 more Smart Citation
“…There are different categories in separation of transcriptome, the common categories separate RNAs based on size [5]. Long non-coding RNAs (lncRNAs) are the class of transcriptome, with size larger than 200 nucleotides [6]. The about lncRNAs which are involved in multiple sclerosis (MS).…”
Section: Introductionmentioning
confidence: 99%